2020
DOI: 10.1186/s12885-019-6507-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of surgical resection for T1b gallbladder cancer: an institutional evaluation

Abstract: Background: There is no comprehensive agreement concerning the overall performance of radical resection for T1b gallbladder cancer (GBC). This research focused on addressing whether T1b GBC may spread loco-regionally and whether radical resection is necessary. Methods: A retrospective analysis was conducted of 1032 patients with GBC who underwent surgical resection at our centre and its affiliated institutions between January 1982 and December 2018. A total of 47 patients with T1b GBC, 29 (62%) of whom underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
(32 reference statements)
0
22
0
9
Order By: Relevance
“…Recently, an international multicenter study analyzed the clinical outcomes of 237 patients with T1b GBC according to the type of surgery (simple versus extended cholecystectomy), and showed that there exist no significant differences in the 5-year overall disease specific survival (DSS) between both treatments, concluding that extended cholecystectomy is not needed for the treatment of T1b GBC [72]. Consistent with this report, Yuza et al [69] evaluated the long-term survival benefit of a surgical procedure in 47 Japanese patients with T1b GBC, showing that both OS and DSS between simple cholecystectomy and radical resection are comparable [69]. A factor that most likely contributes to the conflicting impressions regarding the optimal management of early GBC is the understaging phenomenon that occurs when the surgical specimen is not fully examined (mapped).…”
Section: Pathological Prognostic Markers For Early and Advanced Gallbmentioning
confidence: 65%
See 2 more Smart Citations
“…Recently, an international multicenter study analyzed the clinical outcomes of 237 patients with T1b GBC according to the type of surgery (simple versus extended cholecystectomy), and showed that there exist no significant differences in the 5-year overall disease specific survival (DSS) between both treatments, concluding that extended cholecystectomy is not needed for the treatment of T1b GBC [72]. Consistent with this report, Yuza et al [69] evaluated the long-term survival benefit of a surgical procedure in 47 Japanese patients with T1b GBC, showing that both OS and DSS between simple cholecystectomy and radical resection are comparable [69]. A factor that most likely contributes to the conflicting impressions regarding the optimal management of early GBC is the understaging phenomenon that occurs when the surgical specimen is not fully examined (mapped).…”
Section: Pathological Prognostic Markers For Early and Advanced Gallbmentioning
confidence: 65%
“…The random sampling protocols employed by most Western countries may explain the low survival rates reported in some studies [68,73]. In contrast, studies using surgical specimens subjected to precise pathological examination and mapping of cancer lesions have reported survival rates over 90%, even for T1b cases [69,72,74].…”
Section: Pathological Prognostic Markers For Early and Advanced Gallbmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin beta-1 is mainly expressed in normal cells and in tumor-associated cells, where they control various developing processes, including angiogenesis, tumor progression, apoptosis, and metastasis [ 59 ]. Recently, flow cytometry showed that ITGB1 was expressed at high levels in clear cell renal cell carcinoma [ 60 ]. Transforming protein RhoA (encoded by RHOA gene ) is a small GTPase protein primarily associated with cytoskeleton regulation, mostly actin stress fibers formation and actomyosin contractility [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin beta-1 is mainly expressed in normal cells and in tumor-associated cells, where they control various developing processes, including angiogenesis, tumor progression, apoptosis, and metastasis [ 59 ]. Recently, flow cytometry showed that ITGB1 was expressed at high levels in clear cell renal cell carcinoma [ 60 ].…”
Section: Discussionmentioning
confidence: 99%